Quantitative Trading : Algorithms, Analytics, Data, Models, Optimization /: Algorithms, Analytics, Data, Models, Optimization. (2017) - Guo, Xin; Lai, Tze Leung; Shek, Howard; Wong, Samuel Po-Shing
No abstract available